Elliptic and -Analogs of the Fibonomial Numbers - Bergeron, Nantel; Ceballos, Cesar; Küstner, Josef (Symmetry, Integrability and Geometry: Methods and Applications, 2020)
In 2009, Sagan and Savage introduced a combinatorial model for the Fibonomial numbers, integer numbers that are obtained from the binomial coefficients by replacing each term by its corresponding Fibonacci number. In this paper, we present a combinatorial description for the -analog and elliptic analog of the Fibonomial numbers. This is achieved by introducing some -weights and elliptic weights to a slight modification of the combinatorial model of Sagan and Savage.